H. pylori Pattern Gastritis with Negative Helicobacter Immunohistochemical Stain: Does A Specific Comment in Pathology Report Impact Clinical Management?. (28th October 2021) - Hu, X; Lucas, E; Hammer, S; Gopal, P; Bhalla, A; Panarelli, N; Westerhoff, M; Cheng, J; Nalbantoglu, I
Abstract: Introduction/Objective: The clinical significance of H. pylori (HP) pattern of gastritis with a negative Helicobacter IHC stain on gastric biopsy is unclear. Some pathologists report this pattern in cases that are highly suggestive of HP infection with a comment raising the possibility of HP infection; however, the subsequent clinical management of these patients has not been well described. Methods/Case Report: We conducted a retrospective comparison study of patients with gastric biopsy between 2016 and 2019. Group 1 included patients with chronic active or chronic inactive gastritis and negative HP IHC with a comment stating the gastritis pattern is suggestive of HP. Group 2 included patients with chronic active or chronic inactive gastritis and negative HP IHC with no comment about HP pattern. Results (if a Case Study enter NA): We identified 60 patients in Group 1 which were compared to 63 patients in Group 2. Group 1 more frequently had history of HP (48.3% vs. 29.1%, p<0.05). After diagnosis, Group 1 more frequently received treatment (51.7% vs. 20.6%, p<0.001). Of those who received treatment, Group 1 more frequently received HP treatment (triple or quadruple therapy; 21.7% vs. 1.6%, p<0.001). History of HP did not affect whether a patient was treated (p>0.05). Following post-biopsy HP treatment, more patients in Group 1 received fecal antigen test (23.7% vs. 5.5%, p<0.01). Age, gender, NSAID and PPI use did not differ between groups. Conclusion: Adding the diagnostic comment raising the possibility of HP for patients with HP pattern gastritis with negative HP IHC changes clinical management and it is independent of patients' prior HP history.